At-risk early adolescents profiles in the community: A cluster analysis using the strengths and difficulties questionnaire. (November 2021) - Muratori, Pietro; Paciello, Marinella; Castro, Emanuela; Levantini, Valentina; Masi, Gabriele; Milone, Annarita; Senese, Vincenzo Paolo; Pisano, Simone; Catone, Gennaro
Highlights: Emotional and behavioral problems increase during early adolescence. Callous-unemotional traits characterized cluster with lower prosociality. The predominantly internalizing cluster has a higher percentage of females. A low psychopathology with sub-threshold hyperactivity profile was found. Abstract: Early adolescence, with its several changes and demands, represents a delicate period of life. Several studies highlighted that during early adolescence, emotional and behavioral problems tend to increase. Using a person-centered approach, the present study explored the emotional and behavioral functioning profiles in a sample of Italian preadolescent students. Participants were 2959 youths (1533 males and 1426 females; age 10–14 years); they completed the Strengths and Difficulties Questionnaire (SDQ) and the Inventory of Callous Unemotional traits (ICU). Findings revealed four different profiles: "no psychopathology" (41.5%), "low psychopathology with sub-threshold hyperactivity" (33%), "predominantly internalizing" (19%), and "predominantly externalizing" (6.5%). The two latter clusters are characterized by high levels of SDQ Total Score. The "predominantly internalizing" is distinguished by a higher prevalence of females, and the "predominantly externalizing" by a higher prevalence of males and higher CU traits. A person-oriented approach allowed for identifying subgroups of early adolescents who may significantly vary in their configuration of internalizing and externalizing problems. Such subgroups may reflect youths for whom the creation of prevention and intervention programs could be more tailored.